A parallel multi-modular algorithm for computing Lagrange resolvents - Rennert, Nicolas (Journal of symbolic computation, 2004)
The aim of this paper is to exploit the algorithms of paper Experimental Math. 8 (1999) in order to produce a new algebraic method for computing efficiently absolute Lagrange resolvent, a fundamental tool in constructive algebraic Galois theory. This article is composed of two parts. The main idea of the first part is to break up the calculation of absolute resolvent into smaller computations. Since a multi-resolvent is a factor of a resolvent, the whole resolvent may be computed by means of several multi-resolvents. The idea of the second part is that an irreducible polynomial over Z might be reducible over Z /p Z for certain integer p. So the first part can be applied and then, the Chinese remainder theorem allows to lift up the resolvent over Z .